Influence of cigarette smoking on allergic rhinitis: a comparative study on smokers and non-smokers - Grillo, Calogero; La Mantia, Ignazio; Grillo, Caterina M; Ciprandi, Giorgio; Ragusa, Martina; Andaloro, Claudio (Acta Biomedica Atenei Parmensis, 2019)
It has been described that exposure to tobacco smoke causes worsening of allergic rhinitis symptoms. Otherwise, some studies have demonstrated a negative association between cigarette smoke and allergic rhinitis (AR). Given this inconsistency, this study evaluated the quality of life and immuno-inflammatory parameters in current smokers and nonsmokers suffering from AR. A comparative cross-sectional study was conducted in patients who presented symptoms of AR. Patients were categorized into two groups: current smokers and non-smokers based on salivary cotinine measurements. Primary outcomes were the levels of immuno-inflammatory biomarkers (IgE, IL-4, IL-5, IL-13, IL-17, and IL-33) in serum and nasal lavage and the quality of life assessed by the Mini Rhinoconjunctivitis Quality of Life Questionnaire (MiniRQLQ). Secondary outcomes included salivary cotinine levels, and pulmonary function parameters, such as forced vital capacity (FVC), forced expiratory volume in 1s (FEV1), and FEV1/FVC ratio. Twenty-two patients per group were included in the analysis, with no significant difference regarding demographic characteristics. Statistically significant higher values in salivary cotinine levels (p<0.001) and lower lung function FEV1 (p=0.044) and FEV1/FVC (p=0.047) were found in smokers than in nonsmokers. Only serum IL-33 was significantly different in the 2 groups (p<0.001): smokers had higher values compared to non-smokers. There were no significant differences in MiniRQLQ parameters. Although cigarette smoking was not associated with more severe symptoms, smoking could be associated with increased risk of developing airway remodeling and decreased lung function in AR patients, thus appropriate treatment should be prescribed if smoke avoidance is unfeasible.